Analisis Tingkat Kebisingan Akibat Aktivitas Transportasi Di Pasar Sukaramai Kota Pekanbaru - Rika Lestari; Aryo Sasmita; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increase in vehicle ownership causes transportation activities to increaase. The tendency to increase the number of motorized vehicles operating, will add to the burden of traffic one example is the increase in noise intensity. This study aims to map the pattern of noise distribution and to determine the level of noise that occurs in Jenderal Sudirman street Pekanbaru city by taking data in the form of noise data and several other traffic variables such as vehicle volume and speed. This research was conducted using a Sound Level Meter (SLM) and with a noise mapping method for 2 days, namely on Monday which represents peak hours and Saturdays which represent vehicle quiet hours. The results showed that from 180 measurement points the highest noise level was 97.9 dB which was a point with high traffic volume and the lowest noise level was 68.4 dB which had low traffic volume. Comparison of noise level with KepmenLH No.48 / MENLH / 11/1996 quality standard results obtained 4 points in the Sukaramai Market. Noise mapping using the ArcGis 10.3 software program.From this study it can also be concluded that the greater the volume of the vehicle, the vehicle speed will be lower so as to produce a high noise level, and vice versa so that the volume of the vehicle is directly proportional to the noise level, while the vehicle speed is inversely proportional to the noise levelKeywords: Noise, Traffic, Jenderal Sudirman Street